A Comparative Study of Government and Private School Teachers to Explore the Causes of Absenteeism at Secondary Level in District Bahawalnagar, Punjab, Pakistan - Akhtar, Misbah (Journal of Education and Vocational Research, 2013)
The major objective of the study was to compare the different reasons of absenteeism between private and public school teachers at secondary level in district Bahawalnagar, Punjab, Pakistan. Sample of 160 participants was selected.80 participants were from government schools and 80 were from private schools. A questionnaire was used as a research tool. For the analysis of data percentages were find out. It was find out that government teachers avail more leaves than private teacher. Job security, lenient attitude of principle, different functions in the family, transport problems and illness are the main reasons of the teachers’ absenteeism from school. Teacher of private schools avail less leaves because they feel insecure and are unsatisfied with their jobs and working environment.